Implementation of English Learning Model with Contextual Teaching and Learning (CTL) Approach to Improve Students’ Comprehension - Syamsudin; Naila Rajiha; Afifah Nur Annisa (MODELING: Jurnal Program Studi PGMI, 2024)
This study aims to determine the improvement of English learning outcomes of MTs Negeri 7 Boyolali students through the application of English learning models with the CTL approach. This type of research is Classroom Action Research. The subjects of this study were MTs Negeri 7 Boyolali students with a total of 23 students. The research instruments used were observation, tests and documentation. The result data exposure shows that student learning outcomes experience a significant increase in each cycle which is marked by the sufficient category, the first cycle of student learning completeness is 74% with an average value of 76.4 or 17 students who complete then increases in the second cycle of student learning completeness is 87% with an average value of 85.4 or 20 students who pass to achieve good qualifications. Based on the results obtained, it was concluded that there was a very significant increase in English learning outcomes at MTs Negeri 7 Boyolali through the application of the English language learning model with the CTL approach.